Overcoming Speaking Barrier: The Dynamic of English Debate - Wariyati Wariyati; Muhammad Noer Fadlan; M. Khalid M. Khalid; Azhary Tambusai (UIBU, 2023)
English as a communication has a big role for EFL students. English debate as subject preparation for following national competition among national universities. It provides a challenging to be a good critical speaker. This study was purposed to prove the effectiveness of Debate class implementation as the solving problems of low English Speaking skills. A qualitative research method was implemented by using triangulation as the instrument. The speaking barrier would be the dominant focus that invite more analysis. The research finding showed that there are some speaking barrier owned by students, namely anxiety, articulation, pronunciation, elaborating ideas, vocabulary. The students need a good English speaking competency and convey many ideas in their argument critically. Some phenomenon occurs during the learning process include the confidence and anxiety, vocabulary chosen and also the appropriate statement used in building the argument. The challenge derived the researcher to identify a further research which focus on the tendency found in the learning phenomenon. It answered the curiosity about some problems appear in conveying the argument during the debate chamber.